How entrepreneurship programs can increase the interest of young people to become young entrepreneurs, especially the young generation of the Malay family in Indonesia / Dito Wahyutomoa, Zul Hendrib and Nurmahadic - Wahyutomo, Dito; Hendri, Zul; Hadi, Nurma (Center for Islamic Philantrophy & Social Finance (CIPSF), 2021)
This study analyses the implications of entrepreneurship development programs for the young generation in Indonesia in increasing entrepreneurial knowledge, entrepreneurial skills, and entrepreneurial mentality so as to create competitive business actors. Overall, it can be concluded that entrepreneurship development programs have a positive impact on the creation of competitive business actors. The research results from the researchers prove that the success of the entrepreneurship development program has a positive effect on the addition of entrepreneurial knowledge, and the increase in entrepreneurial skills and the formation of entrepreneurial mentality for business actors starting from the intention to the output process. The role of the millennial generation at this time is very large in building the nation, the way of thinking of the broad millennial generation can make changes and can be a pioneer, not only following existing trends, but can create new things in society. To be able to give birth to young entrepreneurs is not something easy, because it is not only a matter of availability of capital, technology, markets and creativity to be entrepreneurs, but strong entrepreneurial mentality, attitudes and behaviour must be deeply embedded in order to become strong young entrepreneurs.